USAGE OF COMPUTERISED MEANS IN VOCAL ASSESSMENT - Ana RUSU (Studia Universitatis Babeş-Bolyai. Musica)
This study investigates implementation of new technologies in vocal assessment pertaining to university degree artistic education. One of our objectives represents the collection of information regarding changes occurring in singing voice as a result of professional training. This approach fully validates recent research in the field, proving that vocal training has a significant effect on human voice, and close follow-up of the subsequent development brings numerous benefits for both young singers and teachers.